Diphosphino‐Functionalized 1, 8‐Naphthyridines: a Multifaceted Ligand Platform for Boranes and Diboranes. Issue 63 (11th October 2021) - Cui, Jingjing; Dietz, Maximilian; Härterich, Marcel; Fantuzzi, Felipe; Lu, Wei; Dewhurst, Rian D.; Braunschweig, Holger
Abstract: A 1, 8‐naphthyridine diphosphine (NDP) reacts with boron‐containing Lewis acids to generate complexes featuring a number of different naphthyridine bonding modes. When exposed to diborane B2 Br4, NDP underwent self‐deprotonation to afford [NDP‐B2 Br3 ]Br, an unsymmetrical diborane comprised of four fused rings. The reaction of two equivalents of monoborane BBr3 and NDP in a non‐polar solvent provided the simple phosphine‐borane adduct [NDP(BBr3 )2 ], which then underwent intramolecular halide abstraction to furnish the salt [NDP‐BBr2 ][BBr4 ], featuring a different coordination mode from that of [NDP‐B2 Br3 ]Br. Direct deprotonation of NDP by KHMDS or PhCH2 K generates mono‐ and dipotassium reagents, respectively. The monopotassium reagent reacts with one or half an equivalent of B2 (NMe2 )2 Cl2 to afford NDP‐based diboranes with three or four amino substituents. Abstract : Five diphosphino‐functionalized 1, 8‐naphthyridine (NDP)‐based boron compounds were synthesized via two different methods: direct coordination and salt elimination. In these NDP‐based boron compounds, NDP behaves as a flexible, multifaceted ligand. For example, it functions as a tridentate ligand toward B2 Br4 and as a bidentate ligand for BBr3 . Furthermore, NDP binds through only one nitrogen to a diaminodiborane to furnish tri‐ and tetraamino diboranes.